ANALISIS KEGIATAN PRAMUKA DISERTAI LOMBA PUISI TEMA PAHLAWAN DI SMPN MANARAI NO 18 KEPULAUAN SELAYAR - Ratna Deli (SISTEMA: Jurnal Pendidikan, 2023)
Scouting is an activity carried out outside school hours, activities carried out outside school hours have a lot of influence on students' personalities. A good child's personality is very important in learning activities at school. This researcher aims to find out how the implementation of scout activities (poetry competition with the theme of heroes) at SMPN Manarai no 18 Selayar Islands. The method used in this study is a qualitative method, and the technique used is snowball sampling and the subjects of this study include school principals, scout coaches and scout members, while the object of research is the implementation of scout activities at SMPN Manarai no 18 Selayar Islands. The technique used in this research is to use multiple sources for one data by comparing the interview results with the data in the observation documents. Consultations were held with school principals and scout coaches who would carry out scout activities at the research location. The validity of this research data was obtained from the process of comparing the results of interviews with observation and documentation. Based on the results of the research data analysis, the following findings were obtained: (1) the school had prepared a structured program for scouting activities including poetry competition activities before carrying out scouting activities, prepared infrastructure, and the school provided funds from the School Operational Assistance (BOS). (2) in carrying out scouting activities, the scout coach prepares a scouting activity plan which is enlivened by a poetry competition in it so that the scouting activities are in accordance with the Scout General Proficiency Requirements (SKU) book.